2021
DOI: 10.1021/acsnano.1c03635
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Switchable Nanoripples in Ti3C2Tx MXene

Abstract: MXenes are two-dimensional materials with a rich set of chemical and electromagnetic properties, the latter including saturable absorption and intense surface plasmon resonances. To fully harness the functionality of MXenes for applications in optics, electronics, and sensing, it is important to understand the interaction of light with MXenes on atomic and femtosecond dimensions. Here, we use ultrafast electron diffraction and high-resolution electron microscopy to investigate the laser-induced structural dyna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…As the electron temperature decreases with decreasing optical excitation fluence, the effective electron heat capacity also decreases, leading to a shorter τ heating . For instance, we estimated τ heating to be ∼125 fs for an excitation density of 1 mJ cm −2 , which agrees within a factor of 2 with the result of Volkov et al 46 under the same fluence. Of note, recent reports performing transient absorption on Ti 3 C 2 T x have attributed the dynamic optical response on the order of few hundred femtoseconds to solely electron−electron scattering.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…As the electron temperature decreases with decreasing optical excitation fluence, the effective electron heat capacity also decreases, leading to a shorter τ heating . For instance, we estimated τ heating to be ∼125 fs for an excitation density of 1 mJ cm −2 , which agrees within a factor of 2 with the result of Volkov et al 46 under the same fluence. Of note, recent reports performing transient absorption on Ti 3 C 2 T x have attributed the dynamic optical response on the order of few hundred femtoseconds to solely electron−electron scattering.…”
supporting
confidence: 89%
“…(e) Lattice heating time estimated through a two-temperature model as a function of excitation density. The red star denotes the experimental data from this work and green dot denotes the data from Volkov et al46…”
mentioning
confidence: 99%
“…It has been suggested that large polarons are responsible for the extended lifetime of photocarriers and the relatively high mobility of carriers in MXenes . However, ultrafast electron diffraction measurements suggest the presence of strong electron–phonon couplings . Recently, Zhang et al revealed strong couplings between the electron and the A 1g mode, together with weak couplings between the electron and the E g mode, using ultrafast broadband impulsive vibrational spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
“…16 However, ultrafast electron diffraction measurements suggest the presence of strong electron−phonon couplings. 17 Recently, Zhang et al revealed strong couplings between the electron and the A 1g mode, together with weak couplings between the electron and the E g mode, using ultrafast broadband impulsive vibrational spectroscopy. 12 However, the small and large polaron dynamics remain elusive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Considering a decrease in the physical size of matter to a nanoscale level, surface scattering plays an important role, which is beneficial for efficient carrier transfer and energy injection in heterojunctions. Specifically, when the carrier mean free path (MFP) is larger than the radius or thickness of a nanostructure, the effect of the path size on an interfacial carrier and energy transport should be considered. ,, Recently, time-resolved experiments have indicated electron–phonon interaction occurring within 100 fs in two-dimensional (2D)–metal carbides (MXenes), which is faster than graphene, , transition metal dichalcogenides, , and perovskites. , Currently, most theoretical studies of MXene have focused on the intrinsic electron–phonon interaction. The scattering rate has been predicted by considering the following factors: (I) the electron density of states (DOS) near the Fermi surface, (II) the phonon frequency, and (III) the electron–phonon coupling matrix elements, which are relevant to phonon displacement and electron wave function. , However, the size of MXene ranging from 1.5 to 2.0 nm in the out-of-plane direction ( L ⊥ ), , which is comparable to or smaller than the MFP of ∼2 nm, , may result in the occurrence of carrier surface scattering.…”
mentioning
confidence: 99%